Examining the Nutrient Exchange in All Incubation Periods in Chukar Partridges - Kizilaslan, A.; Simsek, U.G. (Agricultural Research Communication Centre, 2022)
Background: This study was conducted to examine the development of the embryo during incubation and the composition, amount and consumption of the egg nutrients among Chukars (Alectoris chukar). Methods: A total of 1210 eggs were carefully separated into their components (albumen, yolk, shell, amniotic-allantoic fluid and embryo) on day 0 (fresh), in the first (day 7), second (day 14) and third (day 21) weeks of incubation and on the hatching date. The moisture, crude protein, crude fat, carbohydrate, crude ash and energy level were determined in egg components. Result: The albumen, yolk, shell, fluid and embryo rates were calculated to be 53.62, 34.84, 11.53, 0.0 and 0.0% in fresh egg, 16.74, 33.49, 16.22, 31.76 and 2.06% in the first week of incubation, 15.65, 28.32, 15.58, 23.35 and 17.10% in the second week of incubation and 0.0, 23.33, 19.38, 0.0 and 57.29% in the third week of incubation, respectively. The hatching weight of the chick was 16.16 g. The nutrients of the yolk, albumen, fluid and shell proportionally varied significantly in different periods of incubation. According to the nutrient changes calculated based on the weight differences of egg components, carbohydrates were mostly used for nutrients during incubation. It was found that even though the nutrients in all the egg components were used in the different periods of incubation, egg yolk was an important source for the embryo throughout the incubation period. © 2022, Agricultural Research Communication Centre. All rights reserved.
Keywords: Egg nutrients; Embryo development; Incubation; Nutrient change; Partridge